EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN STAD ( STUDENT TEAMS ACHIEVEMENT DIVISIONS) PADA MATERI POKOK PERBANDINGAN DAN FUNGSI TRIGONOMETRI DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS X SMA NEGERI SE-KOTA MADIUN - Budi, Wahyu Astuti; Kusmayadi, Tri Atmojo; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of this research was to find out the  effect of learning models (STAD, Jigsaw, and conventional) on mathematics achievement viewed from  learning motivation. The type of research was a quasi experimental research with the factorial design of 3x3. The population was the students in grade X Senior High School in Madiun City. The samples of the research were taken by using the stratified cluster random sampling technique. The samples of the research consisten of 257 students. Instruments used to collect data were prior knowledge test, mathematics achievement test, and motivation quetioner. The trial of instrument test includes of content validity, difficullty level, discrimination power, and reliability. Test requirements included normality test used Lilliefors method and the homogenity test used the Bartlett test. The Balance test used unbalance one way analysis of variance. The hypothesis test used unbalanced two ways analysis of variance. The conclusions of the research were as follows: (1) the STAD and Jigsaw learning models result in the same good learning achievement in mathematics and both result in a better learning achievement in mathematics than the conventional learning model. (2) the learning achievement in mathematics toward high motivation and low one were equally well, high achievement motivation  learning was better than low motivation. (3) for students who taugh by cooperative learning model of STAD, Jigsaw and conventional, the learning achievement in mathematics toward high motivation and low one were equally well, high achievement motivation  learning was better than low motivation. (4) in the each motivation learning the students with high, medium, and low,  the STAD and Jigsaw learning models result in the same good learning achievement in mathematics and both result in a better learning achievement in mathematics than the conventional learning model. Keywords: STAD, Jigsaw, Conventional, learning motivation